Phenotypic and Molecular Detection of Antiseptic Resistance Genes among Clinical Staphylococcus aureus Isolates During COVID-19 Pandemic - Hala Badawi; Alaa Reda; Manal El Said; Amira El-Far; Reham Magdy; Ahmed El-Shenawy; Noha Yousry (Journal of Pure and Applied Microbiology, 2022)
The coronavirus disease (COVID-19) pandemic has expanded the use of chlorhexidine digluconate, a biocide frequently used in hospitals, to inhibit the spread of infection. Genes responsible for resistance against the quaternary ammonium compound qac in Staphylococcus aureus isolates have been shown to confer tolerance to a number of biocidal chemicals, including chlorhexidine. The aim of this study was to determine the occurrence of antiseptic resistance genes (qacA/B and qacC) in clinical isolates of methicillin-susceptible (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA). The study also aimed to investigate the association between the presence of the mecA, qacA/B, and qacC genes in MRSA isolates and the susceptibility of the isolates to chlorhexidine to evaluate its future use in the Theodor Bilharz Research Institute (TBRI) hospital, following the Centers for Disease Control and Prevention recommendations for patients with MRSA. S. aureus isolates (n = 100) were collected from inpatients and outpatients at TBRI. A minimal inhibitory concentration of chlorhexidine was also detected. Polymerase chain reaction was used to detect the mecA, qacA/B, and qacC genes. The results revealed that 84% of S. aureus isolates were MRSA. MRSA (61.9%) and MSSA (68.8%) isolates were susceptible to chlorhexidine. The qacA/B gene was more dominant, being detected in 34%, while qacC was detected in only 5% of S. aureus isolates. All S. aureus isolates with reduced susceptibility to chlorhexidine harbored either the qacA/B or qacC genes. The clinical use of chlorhexidine may continue to increase, emphasizing the significance of continuous caution underlining the emergence of new clones with reduced susceptibility and avoiding antiseptic misuse.